Theoretical analysis and optimization modelling for battery swapping station with grid net-metering - Goh, Benjamin Hong Wei (2017)
The rapid adoption of electric vehicle (EV) technology has created a demand for a supply infrastructure to support these EVs. However, such capital intensive project requires a sustainable business model for its setup. Many researches have focused on building an optimized model through the use of a BSS framework. While their models are shown to be profitable in normal scenarios, they are susceptible to uncertain demand. The aim of this paper is to investigate the influence of adopting a net-metering model in the current proposed BSS framework. By considering net-metering as an option, BSS operators will have greater decision making abilities in the face of uncertain consumer demand. When demand is low, BSS operators will have the option of selling electricity to the grid. This could serve as a buffer against declining profits and also potentially lowers the total cost of operation. In this paper, an optimization model with net-metering capability was developed and tested on simulated case studies. The results obtained clearly showed that the net-metering model has cost saving advantages over a model that did not take net-metering into consideration. The extent to which our results hold true is investigated through comparison and sensitivity analysis. The paper also explores other uses for the model. The model can serves as a basis for making business decisions, like choosing the optimal number of batteries to purchase and analyse the operating efficiency level. The paper briefly touches on the impacts of BSS to grid load profile and ends with recommending that future models should take net-metering into their development framework.